Demonstration of an epitope of the transferrin receptor in human cervical epithelium--a potentially useful cell marker. Issue 2 (February 1984) - Lloyd, J M; O'Dowd, T; Driver, M; Tee, D E
Abstract : The distribution of an epitope of the transferrin receptor in the human uterine cervical epithelium has been investigated. Immunohistochemical staining, both immunofluorescent and immunoperoxidase, was performed on biopsy specimens and cytological samples from normal, dysplastic, and neoplastic cervical epithelia using the monoclonal OKT9 antibody. The results of staining 145 cervical biopsy specimens with OKT9 showed widespread staining in all malignant epithelia and most severely dysplastic epithelia. No such staining was seen in either normal epithelia or in mildly dysplastic epithelia apart from the staining of the basal cell layer in some normal epithelia. The incidence of staining in the 50 cervical cytocentrifuge preparations was not as high as that in the 145 tissue sections. The potential role of the OKT9 antibody in both the screening of cervical cytocentrifuge preparations and the prediction of malignancy is discussed. The antibody is considered to be of more value in the examination of biopsy material than of cytocentrifuge preparations.